2014
DOI: 10.18869/acadpub.mcs.1.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Assessment the preparedness of selected hospital to deal with disasters in Tehran

Abstract: Introduction: disasters are ecological or emergency situations that are most of the organizations and institution's potential. And the resulting to enormous financial and physical losses. Hospitals as the important health institutions should be ready before the events of sufficiently, to be able to cope with emergencies, ensuring rapid response to the incident. Based on a survey to determine the level of preparedness to deal with disasters in one of the selected hospitals in Tehran. Materials and Methods:This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 0 publications
2
29
4
Order By: Relevance
“…Therefore, hospitals should have a pre-designed operational program to cope effectively with disaster-induced emergencies. The absence of such a program will increase the disorder and confusion in the disaster management process [13]. Hospitals lose their ability to provide appropriate health services if they are not prepared or damaged at times of disaster and subsequently, a secondary crisis occurs [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, hospitals should have a pre-designed operational program to cope effectively with disaster-induced emergencies. The absence of such a program will increase the disorder and confusion in the disaster management process [13]. Hospitals lose their ability to provide appropriate health services if they are not prepared or damaged at times of disaster and subsequently, a secondary crisis occurs [9].…”
Section: Introductionmentioning
confidence: 99%
“…Vahedparast et al (2013) in their study showed that the disaster prepared-ness of hospitals in Bushehr Province was very poor [11]. Daneshmandi et al (2014) reported that in hospitals of Tehran, the preparedness of emergency, security, support, staffing, and management departments was at good level, while the department of traffic was at poor level, and units of admission, communication, training, transfer, and discharge were at average level [12].…”
Section: Introductionmentioning
confidence: 99%
“…At times, such incidents also cause injuries, leading to disability or loss of life [1]. Natural disasters of varying intensities often occur in Iran, and the possibility of their occurrence is felt differently in different societies [2,3]. The consequences also include damages caused to both life and property.…”
Section: Introductionmentioning
confidence: 99%